A reinvestigation of a synthetic peptide (TrPepz) designed to mimic trypsin. - Wells, J A (1994)
Recently, a 29-residue cyclic peptide was synthesized (TrPepz) that was reported to possess nearly the same catalytic activity and specificity as the pancreatic serine protease, trypsin, for hydrolysis of a small ester substrate, N-tosyl-L-arginine methyl ester (TAME), and small and large peptides [Atassi, M. Z. & Manshouri, T. (1993) Proc. Natl. Acad Sci. USA 90, 8282-8286]. To study these results we have resynthesized TrPepz and a related cyclic peptide reported to possess some trypsin-like activity. The authenticity of each peptide was confirmed by mass spectrometry, peptide sequencing, compositional analysis, and 1H NMR spectroscopy. However, neither peptide exhibited any detectable esterase activity or amidase activity under a variety of conditions tested. Molecular modeling studies indicated it was possible for TrPepz to be nearly superimposed upon the active site of trypsin. However, NMR experiments showed the structure of the cyclic peptide to be disordered. Thus, we were unable to confirm the results of Atassi and Manshouri. Our results are consistent with the view that serine protease activity depends not only on the presence of catalytic groups but also on their precise and stable alignment.